One More Tool for Understanding Resonance and the Way for a New Definition - Emanuel Gluskin; Doron Shmilovitz; Yoash Levron (Journal of Engineering)
We propose the application of graphical convolution to the analysis of the resonance phenomenon. This time-domain approach encompasses both the finally attained periodic oscillations and the initial transient period. It also provides interesting discussion concerning the analysis of nonsinusoidal waves, based not on frequency analysis but on direct consideration of waveforms, and thus presenting an introduction to Fourier series. Further developing the point of view of graphical convolution, we arrive at a new definition of resonance in terms of time domain.